Incidence of Diabetic Retinopathy Amongst Persons who Screened Positive for Diabetes in five Neighborhood Eye Camps in Northern Multan Pakistan - Ahmad Javed, Asma Mehfooz, Abdullah Choudhry, Nauman Ahmed, Kashaf Shamrez, Hafiz Bilal Bashir, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Lack of community data on diabetes-related blindness in Pakistan. In five neighborhood eye camps in northern Multan, Pakistan, we assessed the incidence of diabetic retinopathy amongst persons who screened positive for diabetes. Methods: In Multan, Pakistan's largest metropolis, five community-based eye camps were created in the May of 2021. Study participants had to be at least 32 years of age. They were tested for diabetes and go to an eye doctor for assessment of their diabetic retinopathy. We identified five eye clinics in Pakistan's largest metropolis, Multan, between May 2020 and April 2021 in Multan eye Hospital. All respondents were required to give verbal informed permission at the time of the assessment. It was determined that diabetic retinopathy was the most important outcome measure, which was classified into no proliferative, serious NPDR, and diabetic nephropathy retinopathy. It must have been predicated on a patient assessment. Results: There were 925 people tested for diabetes. 18% had diabetes: 2.9% had type I and 16.8% had type II. There were 138 individuals who went to the hospital for an ophthalmological checkup. Diabetic Retinopathy was found in 16.8% of the patients. There was a higher increase of diabetic retinopathy among persons with type I diabetes, those who had been diabetic for longer periods of time, and women. One of the most prevalent types of diabetes. Maculopathy (18.7 percent) and proliferative diabetic retinopathy were the two most prevalent forms of diabetic retinopathy, respectively (6.8 percent). Conclusion: We need more systematic study and population-based studies to establish the occurrence of diabetic retinopathy in Pakistan and the potential things that affect to it.